Hybrid hierarchical architecture for integration and interoperability of a one-stop e-government portal / Khairul Anwar Sedek ... [et al.] - Sedek, Khairul Anwar; Omar, Mohd Adib; Sulaiman, Shahida; Osman, Mohd Nizam (UiTM Cawangan Perlis, 2018)
The main function of a one-stop e-government portal is to provide single access point to various e-government services for its users. It needs an effective architecture for integration and interoperability between a one-stop e-government portal and related e-government services. However, due to heterogeneous e-government service platforms and bad e-government service organization, a one-stop e-government portal may fail to provide its main function effectively. This study proposes an architectural approach to improve integration and interoperability among one-stop e-government portal, e-government applications, and e-government services using a service component architecture. The evaluation shows that the proposed approach could be successfully implemented in a prototype of a one-stop e-government portal.